Corpos reinventados: a questão dos gêneros em Freud - Cavalcanti, Rosalia Andrade (2009)
The present paper analyses the theoretical framework that subsidizes the phallic-oedipal Freudian model in order to consider to what extent it reproduces sexual and binary divisions, with its hierarchical and asymmetrical implications. Initially, we have examined philosophical, scientific and political assumptions that permitted the invention of the sexual difference model, producing specific roles to feminine and masculine genders. Afterwards, we have evaluated repercussions from the sexual and phallic monism on the reinvention of sexed bodies. And, finally, we have focused on the construction of the phallic-oedipal model, searching for approximations with monism and sexual dimorphism, as well as its imbrications on subjectivities production. To do so, we have carried out a bibliographical research and analysis of Freudian work and contemporary psychoanalysis by authors who seek to question the implications of the phallicoedipal model utilization as a central axis for subjectivity and eroticization, such as Joel Birman, Márcia Arán, Regina Néri and Silvia Nunes. In the same way, we have established a productive dialogue with authors such as Thomas Laqueur, Michel Foucault and Judith Butler with regards to the creation of sex and gender categories. We expect our work to broaden discussion and knowledge on questions related to sex and gender problematic in contemporaneity, offering support to professionals who deal with those themes directly or indirectly